Society of behavioral medicine statement on COVID-19 and rural health - Behrman, Pamela (Transl Behav Med, 2020)
This position statement provides researchers, practitioners, and policymakers an overview of pre-existing and COVID-related rural health inequities in the United States (U.S.) and how they have been exacerbated by the COVID-19 pandemic. “Health deserts,” defined as “large areas with inadequate or nonexistent medical and trauma facilities,” are common in rural regions of the U.S. While telehealth could address some of these health-related inequities, significant gaps in broadband Internet availability are also common in these more remote areas. The Society of Behavioral Medicine urges Congress to authorize increased funding to rural healthcare facilities and staffing, along with the development of enhanced broadband Internet infrastructure. In addition, incentivizing rural healthcare systems to deliver value-based care could enhance their capacity to implement population health and behavioral health strategies. To stem the spread of COVID-19 in higher-risk rural-based industries (e.g., food processing plants), SBM urges Congress to require the Occupational Safety and Health Administration (OSHA) to routinely inspect for and enforce COVID-19 mitigation procedures, such as provision of effective Personal Protective Equipment (PPE) to all front-line workers and consistent implementation of standardized testing and social distancing advisories. The context of rural communities underscores the importance of tailored approaches to mitigate rural health inequities and promote the well-being of rural residents.